2021
DOI: 10.3892/ijo.2021.5200
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles and mechanisms of microRNA‑222‑3p in human cancer (Review)

Abstract: MicroRNAs (miRNAs/miRs) are a class of small non-coding RNAs that maintain the precise balance of various physiological processes through regulating the function of target mRNAs. Dysregulation of miRNAs is closely associated with various types of human cancer. miR-222-3p is considered a canonical factor affecting the expression and signal transduction of multiple genes involved in tumor occurrence and progression. miR-222-3p in human biofluids, such as urine and plasma, may be a potential biomarker for the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 119 publications
(189 reference statements)
2
17
1
Order By: Relevance
“…However, miR-222 overexpression did not show prognostic significance in our AML-NK group. This is consistent with recent investigation of miR-222 expression, based on data from the Cancer Genome Atlas that also found that high miR-222 expression did not have significant impact on prognosis, and contrary to the oncogenic role of miR-222, the authors reported that high miR-222 expression seemed to indicate a tendency towards longer survival [ 36 ]. Because of the reported negative correlation between GAS5 and miR-222 expression, we performed analysis of the combined influence of GAS5 and miR-222 expression level on prognosis in AML-NK patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, miR-222 overexpression did not show prognostic significance in our AML-NK group. This is consistent with recent investigation of miR-222 expression, based on data from the Cancer Genome Atlas that also found that high miR-222 expression did not have significant impact on prognosis, and contrary to the oncogenic role of miR-222, the authors reported that high miR-222 expression seemed to indicate a tendency towards longer survival [ 36 ]. Because of the reported negative correlation between GAS5 and miR-222 expression, we performed analysis of the combined influence of GAS5 and miR-222 expression level on prognosis in AML-NK patients.…”
Section: Discussionsupporting
confidence: 91%
“…It is well documented that miR-222-3p plays various roles in the initiation, progression, metastasis and treatment response of cancer. It is involved in the regulation of multiple tumor signaling pathways, such as PI3K/AKT, PTEN, JAK/STAT, TRPS1/ZEB1 and EMT [ 36 ]. Several studies have shown that its expression could be a target for innovative cancer therapeutic approaches [ 36 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, only HCV/HIV co-infected grafts showed an up-regulation of miR-222, known to play a role in the inhibition of HIV entry in macrophages by targeting CD4 [ 40 ]. miR-222 is also a well-recognized oncogenic miRNA [ 41 ], known to play a role in hepatocellular carcinoma (HCC), by acting on AKT signaling [ 42 , 43 ]. Additionally, it contributes to liver fibrosis by activating stellate cells [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it contributes to liver fibrosis by activating stellate cells [ 44 , 45 ]. Interestingly, it has been displayed that circulating levels of miR-222 correlate with HCC stage and prognosis [ 41 , 42 , 43 ], suggesting that, also in transplanted patients, miR-222 plasma levels could play a role as biomarkers.…”
Section: Discussionmentioning
confidence: 99%